3D geometric engineering of the double wedge-like electrodes for filament-type RRAM device performance improvement - Sun, Jianxun (2021)
The resistive switching variability and reliability degradation are the two major challenges that hinder the high-volume production of the Resistive Random Access Memory (RRAM) devices. In this work, a 3D electrode structure engineering method is proposed. The geometric parameters defined as electrode angle (EA), electrodes spacing (ES) and electrode trench depth (ETD) associated with the double wedge-like electrodes of the filament-type RRAM devices are studied for the first time. Our experimental results show that apart from the resistive switching uniformity, the reliability performance such as cycling endurance and data retention are significantly improved for the device with small EA (90°), narrow ES (440 nm) and deep ETD (90 nm) owing to the electric field confinement and enhancement. Thus, this new approach can be served as a guideline for the design and optimization of the filament-type RRAM devices.